2023
DOI: 10.3390/v15071516
|View full text |Cite
|
Sign up to set email alerts
|

Infection Dynamics and Genomic Mutations of Hepatitis E Virus in Naturally Infected Pigs on a Farrow-to-Finish Farm in Japan: A Survey from 2012 to 2021

Abstract: Hepatitis E virus (HEV) causes acute or chronic hepatitis in humans. Pigs are the primary reservoir for zoonotic HEV genotypes 3 and 4 worldwide. This study investigated the infection dynamics and genomic mutations of HEV in domestic pigs on a farrow-to-finish pig farm in Japan between 2012 and 2021. A high prevalence of anti-HEV IgG antibodies was noted among pigs on this farm in 2012, when the survey started, and persisted for at least nine years. During 2012–2021, HEV RNA was detected in both serum and feca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 56 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…HEV genotypes 1 and 2 are clearly responsible for human hepatitis, and they are spread through the fecal-oral route via contaminated water in Asia and Africa and in Africa and Mexico, respectively [7]. The incidence of autochthonous HEV infections (predominantly genotypes 3 and 4) is increasing in industrialized countries such as Japan [25][26][27]. The present case supports the previous reports that HEV genotype 3, as well as other genotypes, can induce acute-on-chronic liver failure (ACLF) in patients with underlying liver diseases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…HEV genotypes 1 and 2 are clearly responsible for human hepatitis, and they are spread through the fecal-oral route via contaminated water in Asia and Africa and in Africa and Mexico, respectively [7]. The incidence of autochthonous HEV infections (predominantly genotypes 3 and 4) is increasing in industrialized countries such as Japan [25][26][27]. The present case supports the previous reports that HEV genotype 3, as well as other genotypes, can induce acute-on-chronic liver failure (ACLF) in patients with underlying liver diseases [28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…15 HEV infection occurs via intake of grilled or undercooked pork meat and entrails or of game meat contaminated with HEV. 53,54 It has been suggested that transfusion-associated transmission is a potential risk factor for HEV infection. 42 It was reported that a patient was infected with HEV via transfused blood from 23 voluntary do-…”
Section: Epidemiology Epidemiology and Transmission Routes Of Hev Inf...mentioning
confidence: 99%
“…19 Pigs are the primary reservoirs for zoonotic infection of HEV-3 and HEV-4 in Japan. 13,15,20,36,37,40,53,[73][74][75][76][77][78] Wild boars in Japan also serve as reservoirs of HEV-3 and HEV-4. 28,29,79 HEV-3 was found to infect wild sika deer, 26,30,54,80 wild mongooses, 81 rabbits, 82 and monkeys 83 in Japan.…”
Section: Hev Classification and Its Hostsmentioning
confidence: 99%
“…1c ). However, BLAST analyses showed that WB0567 shares 91.8% nucleotide sequence identity with the strain JMT-Chiba08L detected in a patient in Chiba Prefecture, 91.0% identity with the strain JHS-Kan06L detected in a patient in Kanagawa Prefecture (LC406572), and 92.1%, 91.3% and 90.6% identity with strains swEJM1201802SC, swEJM2100729FC and swj570 detected in swine in Japan [ 20 ] ( Fig. 1c ).…”
mentioning
confidence: 99%